The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15176140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Non-Metallic Inclusions on Bending Fatigue Strength of High-Quality Carbon Constructional Steel Heated in an Industrial Electric Arc Furnace

Abstract: Non-metallic inclusions are one of the many factors influencing the strength of materials operating under variable loads. Their influence on the strength of the material depends not only on the morphology of the impurities themselves, but it is also closely related to the microstructure of the material. This microstructure is the matrix for non-metallic inclusions. This article discusses the results of a study investigating the effect of non-metallic inclusions on the fatigue strength of structural steel durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…They can come from, among others, chipping of furnace and ladle components, from contaminated scrap, or they can be formed in the metallurgical process. Elimination of pollutants is economically justified only up to a certain level [ 13 , 14 , 15 , 16 ]. For many years, the question of what quantity and quality of impurities are acceptable in metal alloys has been raised.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can come from, among others, chipping of furnace and ladle components, from contaminated scrap, or they can be formed in the metallurgical process. Elimination of pollutants is economically justified only up to a certain level [ 13 , 14 , 15 , 16 ]. For many years, the question of what quantity and quality of impurities are acceptable in metal alloys has been raised.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of these studies show that the acceptable contamination of alloys depends on their intended use [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Considering the influence of the same impurities present in low-ductility hard steels [ 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] and in high-ductility steels [ 27 , 28 , 29 , 30 , 31 ], different effects of impurities on steel properties were noted. Comparing the impact of impurities with a specific quantitative and qualitative structure on the properties of steel given in various scientific works, it can be concluded that in steels with a hard, non-deformable microstructure, the probability of negative impact of impurities is higher [ 13 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted on an industrial scale on low-carbon and medium-carbon steel was also presented [18,19]. Study [18] presents the bending fatigue strength of steel hardened and tempered at different temperatures, subject to the relative volume of inclusions.…”
mentioning
confidence: 99%
“…Research conducted on an industrial scale on low-carbon and medium-carbon steel was also presented [18,19]. Study [18] presents the bending fatigue strength of steel hardened and tempered at different temperatures, subject to the relative volume of inclusions. The research shows that the main fraction of non-metallic inclusions is Al 2 O 3 , the most numerous were impurities with a diameter of less than 2 µm, argon refining does not affect the proportion of non-metallic inclusions of large dimensions (with a diameter of over 15 µm), and the influence of non-metallic inclusions on the strength of the steel is also related to the microstructure of the steel constituting the matrix of inclusions.…”
mentioning
confidence: 99%